The Interrelationships Among Informal Institutions, Formal Institutions, and Inward Foreign Direct Investment - Holmes, R. Michael; Miller, Toyah; Hitt, Michael A.; Salmador, M. Paz (Journal of Management, 2013)
This research contributes to institutional theory by examining the influence of informal institutions on formal institutions and the effects of formal institutions on inward foreign direct investment. In particular, the authors integrate prior research from multiple disciplines to identify and to examine the roles of a country’s formal regulatory, political, and economic institutions. The results suggest that the country’s informal institutions, in the form of the cultural dimensions of collectivism and future orientation, shape the country’s formal institutions. In turn, each of the three formal institutions affects the country’s level of inward foreign direct investment differently. To facilitate future research, the authors also provide a set of measures for formal institutions in 50 countries.